Dynastic human capital, inequality and intergenerational mobility - Adrian Adermon; Mikael Lindahl; Mårten Palme (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
We study the importance of the extended family - or the dynasty - for the persistence in human capital inequality across generations. We use data including the entire Swedish population, linking four generations. This data structure enables us to - in addition to parents, grandparents and great grandparents - identify parents' siblings and cousins, as well as their spouses, and the spouses' siblings. We introduce and estimate a new parameter, which we call the intergenerational transmission of dynastic inequality. This parameter measures the between-dynasty variation in intergenerational transmission of human capital. We use three different measures of human capital: years of schooling, family income and an index of occupational status. Our results show that traditional parent-child estimates miss about half of the persistence across generations estimated by the extended model.
Keywords: I24; J62; 330; intergenerational mobility; extended family; dynasty; human capital